Risk Factors for Delirium and Association of Antipsychotic Use with Delirium Progression in Critically Ill Trauma Patients. Issue 5 (May 2023) - Shoulders, Bethany R.; Elsabagh, Sarah; Tam, Douglas J.; Frantz, Amanda M.; Alexander, Kaitlin M.; Voils, Stacy A.
Background: Delirium occurs frequently in critically ill and injured patients and is associated with significant morbidity and mortality. Limited data exists on the risk factors for developing delirium in critically ill trauma patients and the effect of antipsychotic (AP) medications on delirium progression. Objective: The objective of this study is to determine the incidence of delirium in critically ill trauma versus non-trauma surgical patients and determine if the presence of trauma was associated with intensive care unit (ICU) delirium. Secondary outcomes included identifying risk factors for delirium and determining the impact of AP medication use on delirium progression in critically ill trauma patients. Methods: This retrospective review studies adult trauma/surgical ICU patients admitted between May 2017-July 2018 to a level I trauma and tertiary referral center. Regression modeling was used to determine the impact of AP use on delirium-free days. Results: Delirium was more common in critically ill trauma patients versus non-trauma surgical ICU patients [54/157 (34.4%) vs 42/270 (15.6%), P < .001]. Of the 54 trauma patients with delirium, 28 (52%) received an AP medication for delirium treatment and in the multiple linear regression analysis, AP use was significantly associated with fewer delirium-free days ( P = .02). Discussion: Higher admission sequential organ failure assessment scores and increased length of stay were significantly associated with delirium onset in critically ill trauma patients. Use of AP medications for delirium treatment in this population had a negative impact on delirium-free days.